Quinoline‐Conjugated Ruthenacarboranes: Toward Hybrid Drugs with a Dual Mode of Action. (19th November 2019) - Gozzi, Marta; Murganic, Blagoje; Drača, Dijana; Popp, John; Coburger, Peter; Maksimović‐Ivanić, Danijela; Mijatović, Sanja; Hey‐Hawkins, Evamarie
Abstract: The role of autophagy in cancer is often complex, ranging from tumor‐promoting to ‐suppressing effects. In this study, two novel hybrid molecules were designed, containing a ruthenacarborane fragment conjugated with a known modulator of autophagy, namely a quinoline derivative. The complex closo ‐[3‐( η 6 ‐ p ‐cymene)‐1‐(quinolin‐8‐yl‐acetate)‐3, 1, 2‐RuC2 B9 H10 ] (4 ) showed a dual mode of action against the LN229 (human glioblastoma) cell line, where it inhibited tumor‐promoting autophagy, and strongly inhibited cell proliferation, de facto blocking cellular division. These results, together with the tendency to spontaneously form nanoparticles in aqueous solution, make complex 4 a very promising drug candidate for further studies in vivo, for the treatment of autophagy‐prone glioblastomas. Abstract : Blasting glioblastoma : Autophagy has become a very attractive target for the design of novel chemotherapeutic agents. Herein we describe the synthesis, aqueous solution properties, and in vitro biological evaluation of ruthenacarborane complexes conjugated with quinoline derivatives that act as autophagy modulators against both human breast adenocarcinoma (MCF‐7) and human glioblastoma (LN229) cell lines.